PERANCANGAN SISTEM INFORMASI PENGIRIMAN BARANG PADA PT ARIESTA IMPEX LOGISTINDO BERBASIS WEBSITE - Yudianto Yudianto (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Freight forwarding is one of the services that are dangerous to consumers because to send goods from one area to another piece of paper only with proof of receipt of goods sent without knowing the existence and just waiting to hear from the person who received the goods. As the development of information technology through the internet and increasingly fierce competition, companies can use the Internet to expand its services by way of tracking the whereabouts of goods, so that the sender and receiver can know the presence status of goods. PT. Ariesta Impex LOGISTINDO need information systems that can display detailed information such as the user required a price list based on the purpose and size and weight (kg) were transported, tracking the shipment and notify the status of the goods and pickup orders online that allow customers to send items online. The used method is the SDLC (System Development Life Cycle) Key words Freight forwarding, Tracking, SDLC (System Development Life Cycle)